Religious tolerance within captivity: exploring Leo Africanus and Panglima Awang as heteroglot travel novels - Firuz-Akhtar Lubis, (Penerbit Universiti Kebangsaan Malaysia, 2023)
The travel novels, "Leo Africanus" by Amin Maalouf and "Panglima Awang" by Harun Aminurrashid share similarities as fictional narratives inspired by real sixteenth-century captives. Focusing on the experiences of the protagonists, Leo and Awang, who were taken captive by colonisers during the 16th century, the novels portray the role of religion as a pathway to freedom, personal growth, and spiritual enlightenment. Through the lens of Bakhtin's heteroglossia and dialogism theory, this study explores how religious discourses interact within the narratives, examining conflicts, harmonies, and transformations. The analysis reveals how "Leo Africanus” and “Panglima Awang" promote religious tolerance through religious diversity and religious concealment, thus challenging rigid beliefs. In conclusion, despite the theme of physical captivity, these travel novels convey a message of acceptance and understanding, showcasing the potential for harmony and mutual respect among different religious perspectives.